25(OH)D3 levels relative to muscle strength and maximum oxygen uptake in athletes - Ksiazek, A.; Zagrodna, A.; Dziubek, W.; Pietraszewski, B.; Ochmann, B.; Slowinska-Lisowska, M. (Journal of Human Kinetics, 2016)
Vitamin D is mainly known for its effects on the bone and calcium metabolism. The discovery of Vitamin D receptors in many extraskeletal cells suggests that it may also play a significant role in other organs and systems. The aim of our study was to assess the relationship between 25(OH)D3 levels, lower limb isokinetic strength and maximum oxygen uptake in well-trained professional football players. We enrolled 43 Polish premier league soccer players. The mean age was 22.7±5.3 years. Our study showed decreased serum 25(OH)D3 levels in 74.4% of the professional players. The results also demonstrated a lack of statistically significant correlation between 25(OH)D3 levels and lower limb muscle strength with the exception of peak torque of the left knee extensors at an angular velocity of 150°/s (r=0.41). No significant correlations were found between hand grip strength and maximum oxygen uptake. Based on our study we concluded that in well-trained professional soccer players, there was no correlation between serum levels of 25(OH)D3 and muscle strength or maximum oxygen uptake.